The Feel of the City: Experiences of Urban Transformation - Kenny, Nicolas (University of Toronto Press, Scholarly Publishing Division, 2014)
At the start of the twentieth century, the modern metropolis was a riot of sensation. City dwellers lived in an environment filled with smoky factories, crowded homes, and lively thoroughfares. Sights, sounds, and smells flooded their senses, while changing conceptions of health and decorum forced many to rethink their most banal gestures, from the way they negotiated speeding traffic to the use they made of public washrooms. The Feel of the Cityexposes the sensory experiences of city-dwellers in Montreal and Brussels at the turn of the century and the ways in which these shaped the social and cultural significance of urban space. Using the experiences of municipal officials, urban planners, hygienists, workers, writers, artists, and ordinary citizens, Nicolas Kenny explores the implications of the senses for our understanding of modernity.